Método de inferência espacial para o ordenamento territorial de municípios de pequeno porte: o caso de Ijaci, MG - Moras Filho, Luiz Otávio (2015)
Territorial planning is considered an essential instrument for sustainable municipal development, becauseit supports the creation of public policies aimed at urban, rural and industrial infrastructure, conciliated to environment preservation. In view of this, the present study evaluated the suitability and restrictions for urban development in the city of Ijaci - MG, through the Additive Multicriteria Method by Weighted Overlay, with the assistance of GIS. In the evaluation of favorable areas were used the following criteria, modeled by fuzzy logic: slope, land use and land cover, distance to the populous areas and to the main roads. Simultaneously, restrictions were modeled by Boolean logic representing the Permanent Preservation Areas, Environmental Protection Zones, Industrial Zones and right-of-wayareas along railroads and highways. As a result, descriptive maps of the area with degrees of suitability for urban development ranging from 0 (unable) to 9 (able) were generated, showing that in this city 56.55% of 105,246 km² surface were considered unsuitable, and 3.49% low suitability.